Liquid-phase hydrogenation of unsaturated aldehydes: enhancing selectivity of multiwalled carbon nanotube-supported catalysts by thermal activation - Bruno F. Machado (2010)
Platinum and iridium organometallic precursors are used to prepare nanosized, thermally stable multiwalled carbon nanotube-supported catalysts. The materials are characterized by N-2 adsorption at 77 K, temperature-programmed desorption coupled with mass spectrometry, H-2 chemisorption, transmission electron microscopy and thermogravimetric analysis; they are tested in the selective hydrogenation of cinnamaldehyde to cinnamyl alcohol under mild conditions (363 K and 1 MPa). A thermal activation at 973 K is found to have a very positive